Use of associated gas in oil well pads, study case Sacha field - Cusanguá-Cisneros, Yessica Ximena (2021)
Ecuadorian’s Amazon region in many oil well PADs the associated gas is burned causing environmental problems, socio-environmental conflicts, loss of energy and uncontrolled emissions CO2. This study gives the opportunity to take advantage the gas for any oil well PADs that is required to carry out the analysis, was realized for the Sacha field, located in the Ecuadorian’s Amazon region. Currently the gas is being burned through change of parameters such as pressure in order to handle gas from a production oil well PADs to central production facilities with the artificial lift available. The information necessary was data reservoir, design installed equipment and surface facilities. The current bottom and surface designs were adjusted meaning the production scenario. Then the pressure required in each oil well PADs was modified to adjust to the electrosubmersible pump design. The gas coming from the annular space was considered to compress and redirect to the production line at the new pressure required. Of the 23 existing wells in the 3 oil well PADs, all the well equipment was adjusted to the new pressure requirement, obtaining 21 equipment adjusted by modifying the frequency to an average of 4 Hz and 2 equipment could not be adjusted due to limitation of stages. The volume gas advantage was the 2.006 MSCFD for a period of 6 years, there would be a saving of $ 5’935.120 in electricity generation and the sale of carbon credits stopping 241.121 tons of CO2.